Functional Characterization of a Ketoreductase-Encoding Gene med-ORF12 Involved in the Formation of a Stereospecific Pyran Ring during the Biosynthesis of an Antitumor Antibiotic Medermycin - He, Qiang; Li, Le; Yang, Tingting; Li, Ruijuan; Li, Aiying (PLOS ONE, 2015)
Medermycin, a polyketide antibiotic, possesses strong bioactivity against a variety of tumors through a novel mechanism and is structurally featured with a pyran ring containing two chiral centers (3S and 15R). By far the biosynthetic origin of such enantiomerical conformations still remains obscure. In the present study, we reported the functional characterization of a proposed ketoreductase Med-ORF12 encoded by medermycin biosynthetic cluster and revealed its involvement in the stereochemical control at C3 center of medermycin. Firstly, bioinformatics analysis of Med-ORF12 suggested that it belongs to a group of stereospecific ketoreductases. Next, a Med-ORF12-deficient mutant was obtained and LC/MS measurements demonstrated that medermycin production was completely abolished in this mutant. Meanwhile, it was found that two shunt products were accumulated at the absence of Med-ORF12. Finally, the reintroduction of Med-ORF12 into this mutant could restore the production of medermycin. In a conclusion, these data supported that Med-ORF12 is essential for the biosynthesis of medermycin and performs its role as a stereospecifc ketoreductase in the tailoring steps of medermycin biosynthetic pathway.